1995
DOI: 10.1063/1.113129
|View full text |Cite
|
Sign up to set email alerts
|

Optical property of GaAsP/AlGaAs strained-layer quantum well grown on GaAs-(111)B substrate

Abstract: GaAs1−xPx/AlyGa1−yAs (x=0.07–0.15, y=0.3) strained-layer quantum wells have been grown on GaAs-(111)B substrates by low-pressure metalorganic vapor phase epitaxy and characterized by photoluminescence (PL) spectroscopy. Evident energy blue shifts of the excitonic transition peaks (some of them as large as 33 meV) were achieved by increasing the excitation power during the PL measurement. The large optical nonlinearity mainly due to the strain-induced piezoelectric field screened by the photoexcited carriers, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The GaAsP-GaAlAs strained-layer quantum well grown on a GaAs substrate is of technological significance, mainly because of its large optical nonlinearity. Zhang et al [1] have demonstrated that the excitonic transition peaks can achieve an energy blue-shift as large as 33 meV during photoluminescence measurements. Thus the GaAsP-GaAlAs strainedlayer quantum well is a good candidate for making optoelectronic devices such as optical switches and modulators.…”
mentioning
confidence: 99%
“…The GaAsP-GaAlAs strained-layer quantum well grown on a GaAs substrate is of technological significance, mainly because of its large optical nonlinearity. Zhang et al [1] have demonstrated that the excitonic transition peaks can achieve an energy blue-shift as large as 33 meV during photoluminescence measurements. Thus the GaAsP-GaAlAs strainedlayer quantum well is a good candidate for making optoelectronic devices such as optical switches and modulators.…”
mentioning
confidence: 99%
“…The MOVPE growth conditions for the ͑GaAsP͒-͑GaAs/AlGaAs MQWs͒-͑GaAsP͒-͑GaAs/AlGaAs MQWs͒-͑GaAsP͒ t-u-t-u-t quantum structure are similar to the ones for the ͑111͒-GaAsP/AlGaAs strainedlayer quantum well structures, which are described in detail in Ref. 11. Figure 2 demonstrates the schematic of GaAs 1Ϫx P x -GaAs/Al y Ga 1Ϫy As MQWs-GaAs 1Ϫx P x -GaAs/ Al y Ga 1Ϫy As MQWs-GaAs 1Ϫx P x ͑xϭ0.15, yϭ0.3͒ t-u-t-u-t quantum structure.…”
Section: ͓S0003-6951͑97͒01239-4͔mentioning
confidence: 94%
“…In other words, it is possible to make fully optically operated devices by using these ͑111͒-oriented strained-layer quantum well structures. In an earlier letter, 11 we reported a detailed photoluminescence ͑PL͒ study on the ͑111͒-GaAsP/AlGaAs strained-layer quantum well structures which has an obvious advantage over the most extensively studied ͑111͒-InGaAs/GaAs quantum well system, in that the strain or the strain-induced electric field in the quantum wells and the energy band offset at the heterointerface can be adjusted independently of each other by changing the phosphorus and aluminum composition, respectively.…”
Section: ͓S0003-6951͑97͒01239-4͔mentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic and optical properties can be significantly modified by the strain effects and in fact, these properties are improved with the inclusion of strain effects [3]. GaAsP quantum well structures have been grown by means of MOVPE and the strain-induced piezoelectric field has been studied and it is found that it can be adjusted by the energy band offset [4]. The optical properties of tensile-strained GaAsP/GaInP square quantum wells grown by MOCVD have been investigated with various characteristics of the PL spectra [5].…”
Section: Introductionmentioning
confidence: 99%